Detection of Label-Free Drugs within Brain Tissue Using Orbitrap Secondary Ion Mass Spectrometry as a Complement to Neuro-Oncological Drug Delivery - Phoebe McCrorie; Jonathan Rowlinson; David J. Scurr; Maria Marlow; Ruman Rahman (Pharmaceutics, 2022)
Historically, pre-clinical neuro-oncological drug delivery studies have exhaustively relied upon overall animal survival as an exclusive measure of efficacy. However, with no adopted methodology to both image and quantitate brain parenchyma penetration of label-free drugs, an absence of efficacy typically hampers clinical translational potential, rather than encourage re-formulation of drug compounds using nanocarriers to achieve greater tissue penetration. OrbiSIMS, a next-generation analytical instrument for label-free imaging, combines the high resolving power of an OrbiTrapTM mass spectrometer with the relatively high spatial resolution of secondary ion mass spectrometry. Here, we develop an ex vivo pipeline using OrbiSIMS to accurately detect brain penetration of drug compounds. Secondary ion spectra were acquired for a panel of drugs (etoposide, olaparib, gemcitabine, vorinostat and dasatinib) under preclinical consideration for the treatment of isocitrate dehydrogenase-1 wild-type glioblastoma. Each drug demonstrated diagnostic secondary ions (all present molecular ions [M-H]− which could be discriminated from brain analytes when spiked at >20 µg/mg tissue. Olaparib/dasatinib and olaparib/etoposide dual combinations are shown as exemplars for the capability of OrbiSIMS to discriminate distinct drug ions simultaneously. Furthermore, we demonstrate the imaging capability of OrbiSIMS to simultaneously illustrate label-free drug location and brain chemistry. Our work encourages the neuro-oncology community to consider mass spectrometry imaging modalities to complement in vivo efficacy studies, as an analytical tool to assess brain distribution of systemically administered drugs, or localised brain penetration of drugs released from micro- or nano-scale biomaterials.